Decoding the Visual and Theoretical Blind Spots in Islamic Advertising: A Bibliometric Synthesis (2015–2025) - Robby Milana (Academic Journal of Da'wa and Communication, 2025)
Over the past decade, Islamic advertising has gained academic attention, yet its theoretical and visual aspects remain underexplored. This study conducts a bibliometric synthesis of 90 peer-reviewed articles (2015–2025) retrieved from Dimensions.ai using a Boolean search combining “Islamic advertising” OR “Halal advertising” with symbolic and theoretical terms. Data were analyzed through VOSviewer 1.6.20 to map trends, collaboration, citation, and thematic clusters. The bibliometric approach was chosen for its capacity to identify conceptual and representational gaps beyond qualitative reviews. Findings show a dominance of behavioral and ethical models, while communication theory, visual semiotics, and audience reception remain marginal. Future studies are encouraged to integrate akhlaq and maslahah with communication and visual theory to enrich symbolic and audience-centered perspectives on Islamic advertising.